El uso de las tecnologías de la información y la comunicación, su aplicación en los procesos educativos en el sistema de nivelación de la Universidad Técnica de Cotopaxi. Propuesta de un manual de las tecnologías de la información y la comunicación en educación. - Cevallos Laverde, Luis Bolívar (2015)
The construction of an alternative college, with a vision of future don´t be understood as an approach to handle a speech but must respond to a bottom-up process, so that the Technical University of Cotopaxi is determined to push important changes in its institutional life, to locate you in the need to accredit their programs and settle at the place it deserves site. Fort that reason I present this research work concerns the use of information technology and communication as an alternative model for students the leveling system to achieve the stablish objectives. This work is based on the need to implement the use of TICs in classrooms, starting with the same problem arising, problem formulation, the rationale, aims and general objectives. The theoretical framework is then developed with issues related to new information technologies and communications and its use to improve the teaching-learning process. Next the methodology is discussed for the investigative process; a description of the technical methods of data collection is made population and sample that formed the basis for the development of analysis and interpretation of results of surveys of teachers and students of the leveling system Extension La Maná that allowed us to verify the hypothesis stablished and come to the conclusions and recommendations. After that proposal, is developed the same consisting of a handbook of information technology and communications that will improve the performance of students in the leveling system and raise the quality of education at the Technical University of Cotopaxi develops.